Effects of Biomass Moisture Content and Process Temperature on Biopellet Quality Derived from Rubber Seed Shell and Ater Bamboo (Gigantochloa atter) - I Dewa Gede Putra Prabawa (Kementerian Perindustrian, 2018)
The purposes of this research were to study the ieffects of biomass moisture content and process temperature on the quality of biopellet derived from rubber seed shell and bamboo ater (Gigantochloa atter). The biomass was conditioned at different moisture contents (6, 12, 14, 16, 18, and 20% w/w), and the biopelet was produced at a pressure of 597,24 kg/cm2 with various process temperatures (100, 125, 150, 175, and 200oC). The results showed that the properties of produced biopellets were significantly affected by the variation of moisture content and process temperature. High moisture content of biomass could increase the moisture content of biopellet while the calorific value and ash content decreased. With the increase in process temperatures, calorific value and ash increased whereas the moisture content of biopellet decreased. Mechanical durability was enhanced with the increase inthe moisture content of biomass, starting from 6% to 18%;and was improved with the increase in the process temperatures, starting from 100oC to 175oC. However, the bulk density of biopellet increased with the increase inthe moisture content of biomass, starting from 6% to 16%, and was improved with the increase in the process temperatures from 100oC to 150oC. The best quality of biopellet was produced in the biomass moisture content of 16% and the process temperature of 150oC. That biopellet had mechanical durability of 99.16%, calorific value of 4,402 cal/g, bulk density of 1,157 kg/m3, moisture content of 6.71%, ash of 1.19%, nitrogen of 0.15%, Sulphur of 0.013%, and chlorine of <0.1 ppm. That biopellet quality met European standards (EN 14961-2).